Embryonic expression of the divergent Drosophila beta3-tubulin isoform is required for larval behavior. - Dettman, R W (2001)
We have sought to define the developmental and cellular roles played by differential expression of distinct beta-tubulins. Drosophila beta3-tubulin (beta3) is a structurally divergent isoform transiently expressed during midembryogenesis. Severe beta3 mutations cause larval lethality resulting from failed gut function and consequent starvation. However, mutant larvae also display behavioral abnormalities consistent with defective sensory perception. We identified embryonic beta3 expression in several previously undefined sites, including different types of sensory organs. We conclude that abnormalities in foraging behavior and photoresponsiveness exhibited by prelethal mutant larvae reflect defective beta3 function in the embryo during development of chordotonal and other mechanosensory organs and of Bolwig's organ and nerve. We show that microtubule organization in the cap cells of chordotonal organs is altered in mutant larvae. Thus transient zygotic beta3 expression has permanent consequences for the architecture of the cap cell microtubule cytoskeleton in the larval sensilla, even when beta3 is no longer present. Our data provide a link between the microtubule cytoskeleton in embryogenesis and the behavioral phenotype manifested as defective proprioreception at the larval stage.